Analisa Keragaman Nilai Kekerasan Baja St-42 Melalui Proses Karburasi Menggunakan Komposisi BaCO3 Dan Carbon Dengan Variasi Waktu Penahanan - Nanse H. Pattiasina; Nevada J.M. Nanulaitta; Steanly R.R. Pattiselanno (ARIKA, 2011)
Pack carburizing is a method of thermo chemical treatment, when carbon dissolved in steel surfaces, revolve 0.3% - 0.9% with temperature between 825 oC - 925 oC, and keep it at several time and then continued with quenching process using water, oil, air or salt. This research had arranged to test the hardness of low carbon steel (ST-42) with 40% of BaCO3, and 60% of Carbon, before and after carburizing process in 3 type of holding time: 15, 30, and 50 minutes. Based on results, the best combination to reach a higher value of hardness provides by combination of after carburizing process and 50 minutes of holding time. Later, an extensive experiment by 2 hours of burning had shown an increase level of hardness up to 365% from the initial condition which proves the quality of this best treatment combination.